Evaluation of partogram in 100 cases of both primi and multi gravida each, their outcome in labour and perinatal outcome - Krishna, K. Sowmya; Paladi, Rajshree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: the objective of this study was to study the utility of partogram in both primi and multi gravida and evaluate its role in preventing prolonged labour; assess the rate of cervical dilatation on admission, and to evaluate the maternal and perinatal outcome by comparing their partogram in labour. Methods: This observational prospective clinical study involved randomly selected 200 patients in labor divided into 2 groups of 100 each admitted in Khaja Banda Nawaz Institute of Medical Sciences, Gulbarga. Modified WHO partogram was used. Statistical analysis done by Chi square test. Results: Mean age group in primi was 22.05 years with standard deviation of 2.38 years and in multi mean age group was 25.19 years with standard deviation of 3.09 years. Mean duration of active phase of labor in primi was 2 hrs 12 mins and in multi was 1 hours and 35 mins from time of admission into hospital. Mean duration of second stage of labor in primi was 57 mins and in multi was 35 mins. Out of 100 primi gravida 68% had NVD, 1% had outlet forceps. 13% had vacuum application and 18% underwent LSCS. Out of 100 multigravida 86% had NVD, 1% had outlet forceps, 7% had vacuum application and 6% underwent LSCS. In group A in primi 75% had NVD, 0% had forceps, 5% had vacuum application and 0% LSCS whereas in multi 93% had NVD and 7% had vaccum, NO forceps /LSCS. In group B, in primi 20% had NVD, 4% had forceps, 33% had vacuum application and 43% had LSCS whereas in multi 34% had NVD, 8% had forceps, 8% had vacuum application and 50% LSCS. In group C, in primi 100% had LSCS whereas in multi there were no NVD/Vaccum/ forceps/ LSCS cases. In primi 100% and in multi 96% had no maternal complications. In primi 96% and in multi 97% had no neonatal complications. Conclusions: The partogram is used to assess the labor progress and identify when intervention is necessary. This study showed that it can be highly effective in reducing complications from prolonged labor for both mother & neonate, in reducing operative intervention and improving their outcome.